2020
DOI: 10.3390/agronomy10030338
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Dry Matter Production and Grain Yield of Dual-Purpose Winter Wheat Using Field Experiment and Modelling

Abstract: The potential of a winter wheat (Triticum aestivum L.) cultivar Wedgetail to provide grazing and grain yield under different sowing times, grazing times, and watering regimes, under current and future climate, was investigated using field experiment and simulation modelling. For the field experiment, there were two watering treatments (unirrigated (D) and irrigated (I)) and four simulated grazing treatments (ungrazed, simulated grazed at growth stage (GS) 25, simulated grazed at growth stage (GS) 32, and graze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These findings were consistent with results reported in Mohanty et al (2012) which showed that the prediction of SWC by APSIM-wheat was relatively accurate (RMSEs in the 0-15 cm soil layer were below 0.04 m 3 .m -3 ) in non-water stress conditions. In contrast, a weak prediction of SWC in the soil surface layer by APSIM-wheat was reported in Australia, in dry conditions with only 160 mm in-season rainfall (Zeleke 2020). In Zeleke's work, APSIM-wheat was also found to overestimate SWC in the surface layer (i.e., 0-15 cm) in unirrigated and irrigated plots.…”
Section: Model Evaluationmentioning
confidence: 85%
“…These findings were consistent with results reported in Mohanty et al (2012) which showed that the prediction of SWC by APSIM-wheat was relatively accurate (RMSEs in the 0-15 cm soil layer were below 0.04 m 3 .m -3 ) in non-water stress conditions. In contrast, a weak prediction of SWC in the soil surface layer by APSIM-wheat was reported in Australia, in dry conditions with only 160 mm in-season rainfall (Zeleke 2020). In Zeleke's work, APSIM-wheat was also found to overestimate SWC in the surface layer (i.e., 0-15 cm) in unirrigated and irrigated plots.…”
Section: Model Evaluationmentioning
confidence: 85%
“…This study shows that understanding soil processes and adapting agricultural management could allow for greater SOC storage, while improving pasture quality. In "Evaluating Dry Matter Production and Grain Yield of Dual-Purpose Winter Wheat Using Field Experiment and Modelling" by Ketema Tilahun Zeleke [8], the potential of 'Wedgetail' winter wheat to provide grazing and grain yield under various conditions in Australia was analyzed. The experiment involved variations in sowing times, grazing times, and watering regimes under present and future climate scenarios.…”
mentioning
confidence: 99%